HEART PROTECTION AGAINST ISCHEMIC LESIONS: THE ROLE OF STRESS-LIMITING SYSTEMS AND STABILIZING MYOCARDIAL STRUCTURE - F. Z. Meerson (Российский кардиологический журнал, 2001)
Heart protection against ischemic lesions: the role of stress-limiting systems and stabilizing myocardial structure.